AB0491 Fatigue is an independent variable predicting physical function and DAS-28 remission for patients with rheumatoid arthritis treated with intravenously administered golimumab: results from phase 3, placebo controlled clinical trial. (23rd January 2014) - Westhovens, R.; Weinblatt, M.E.; Han, C.; Gathany, T.; Kim, L.; Mack, M.; Lu, J.; Baker, D.; Mendelsohn, A.M.; Bingham, C.O.
Abstract : Objectives: To evaluate the association of fatigue with physical function and disease activity in patients with rheumatoid arthritis (RA), and the impact of treatment with intravenously administered golimumab (GLM) on fatigue using data from the Phase III clinical trial GO-FURTHER. Methods: GO-FURTHER was a multicenter, randomized, placebo-controlled study. Adult patients with active RA despite MTX therapy were randomized to placebo + MTX (placebo group) or GLM 2mg/kg plus MTX (GLM group) at week 0, 2, and every 8 week thereafter. Patients in placebo group with <10% improvement in tender and swollen joint count from baseline at week 16 entered early escape and received a 2 mg/kg GLM infusion at Weeks 16 and 20. Impact on physical function was assessed using the disability index of the Health Assessment Questionnaire (HAQ). Fatigue was measured using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) questionnaire, and clinically meaningful improvement in FACIT-Fatigue was defined as ≥4 points increase in the scores.Correlation of FACIT-Fatigue with HAQ and disease activity and remission (DAS28 using CRP<2.6) were analyzed using Pearson correlation, or multiple linear and logistic regression models to adjust for other confounding variables (age, CRP, swollen and tender joints counts). Comparisons between groups were performed using ANOVA on van der Waerden normal scores for continuous outcomes or Chi-square test for binary outcomes. Results: At baseline, mean (SD) FACIT-Fatigue score was 25.5 (10.54), indicating significant fatigue. Significant correlations of FACIT-Fatigue with HAQ (r=-0.62, p<0.01) and DAS28 score (r=-0.42, p<0.01) were observed at baseline. In multiple regression models, baseline FACIT-Fatigue score or change in FACIT-Fatigue at week 24 were correlated with change in HAQ and DAS28 score. Patients with higher FACIT-Fatigue scores at baseline were more likely to achieve DAS28 remission at week 24 (p=0.024). Compared to the placebo group, GLM-treated patients had significantly greater improvement in FACIT-fatigue at week 12 (5.4±10.3 vs. 2.1±9.0), which was sustained through week 16 (7.5±10.5 vs. 2.2±9.7) and 24 (8.0±10.8 vs. 2.5±10.2) (all p-values<0.001). Compared with the placebo group, a greater proportion of patients in the GLM group achieved clinically meaningful improvement in FACIT-Fatigue score at week 12 (57.5% vs. 42.8%) and at week 24 (65.8% vs. 40.3) (all p-values<0.001). Conclusions: RA patients inadequately responsive to MTX experienced severe fatigue. Fatigue was a significant independent predictor of physical function and disease activity in patients with RA. Treatment with intravenously administered GLM significantly improved clinical symptoms of fatigue in patients with RA inadequately responsive to MTX. Disclosure of Interest: R. Westhovens Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, M. Weinblatt Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, C. Han Employee of: Johnson & Johnson Pharmaceutical Services, LLC, T. Gathany Employee of: Johnson & Johnson Pharmaceutical Services, LLC, L. Kim Employee of: Janssen Research & Development, LLC, M. Mack Employee of: Janssen Research & Development, LLC, J. Lu Employee of: Janssen Research & Development, LLC, D. Baker Employee of: Janssen Research & Development, LLC, A. Mendelsohn Employee of: Janssen Research & Development, LLC, C. Bingham III Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study